Stili v detskoi odezhde - Boltubaeva N. I. (Interactive science, 2024)
The article discusses the issues of clothing style for children, how to choose the right wardrobe for children.The distinctive features of modern style trends are given.
Keywords: дизайн; тенденция; мода; коллекция; стиль одежды; collection; image; fashion; design; style; trend; fashion designer; clothing; textile materials; wardrobe; outfit; текстильные материалы; дизайнер-модельер; гардероб